The Effect of Physics Learning Based on Case Method on Skills in Inferences Problems Temperature and Health - Sherly Nur Laili; Sudarti Sudarti; Bambang Supriadi (Pascasarjana, Mataram University, 2023)
The case method is a way of presenting subject matter using a case study flow. This study aims to examine the effect of case method-based physics learning on skills in inferential heat and temperature problems in high school. The type of research used is an experimental design with cluster random sampling data collection method. The data analysis technique used is comparative statistical analysis with the normal distribution test, homogeneity test, One-Way Anova test, and independent sample t-test. The results showed that the average value of inference indicators in critical thinking skills differed significantly between the control and experimental classes. The control class got an average of 3.24 while the experimental class got 4.62. Conclusion: physics learning based on the case method affects skills in inferential heat and temperature problems in high school